Economics, econometrics and the LINK essays in honor of Lawrence R. Klein - Klein, Lawrence Robert; Dutta, Manoranjan (Contributions to economic analysis ;, 1995)
Economics, Econometrics and The LINK is a collection of scholarly contributions by leading scholars from the U.S., Europe, and Asia dealing with issues of economics and econometrics. The book contains a learned and erudite exposition of macroeconomics and macroeconomic modeling including national, sectoral, issues exchange rate, environment, international price competitiveness and international linkages. It presents a comprehensive perspective of econometric modeling - country-specific, sector-specific and issue-specific. The volume is a tribute to the work of Lawrence R. Klein from all his friends who share a common agenda, viz. to relate the study of economics to the studies of mankind.